Improving Teenage Awareness of Healthy Behavior by Mapping Adolescent Programming and Measurement (MAPM) Framework - Siyam, Nur; Cahyati, Widya Hary; Handayani, Oktia Woro Kasmini; Fauzi, Lukman (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
The improvement of healthy behavior awareness of teenagers is still a serious concern. There are three major problems in teenage: sexuality, drugs, and addictive substance and sexually transmitted diseases, especially HIV and AIDS. Among steps that can be taken to build teenage awareness to have healthy behavior is by applying Mapping Adolescent Programming and Measurement (MAPM) Framework. The objective of the research is to build an MAPM Framework model and obtaining a description of its effectiveness as an effort to improve teenage awareness of healthy behavior. The research conducted at Walisongo Kedungwuni Islamic Junior High School. Samples are students that have problem as mapped and measured from MAPM.Ã‚Â  A non-randomized one group pre-test- post-test design was implemented in this study. The results indicate that attitude towards counseling, cigarette, juvenile delinquency, smoking attitude, attitude towards drugs, and premarital sex after the application of the MAPM positively changed (p-value <0,05). The attitude and behavior of students were improved. Teenage awareness of healthy behavior significantly increases (p value= 0,000) after the application of the MAPM framework. Further discussion will be discussed in the article below.